Teaching Coding and Robotics to Young Learners – Instructional Support in Teacher-Child Interaction - Korkeaniemi, Arttu (My University, 2025)
The National Core Curriculum for Early Childhood Education and Care (ECEC) and pre-primary education in Finland requires integration of technological content for young learners’ educational settings. Coding and educational robotics (ER) are also highlighted in Finnish basic education’s subject of Craft, Design, and Technology (CDT). Therefore, early exposure for technological content, such as ER, eases the process for knowledge building of technological literacy needed during later educational stages. This study investigates teacher-child interaction (TCI), especially instructional support, in the context of coding and ER education in Finnish pre-primary education. The study’s theoretical background is framed from research in TCI including three domains of interaction: emotional support, classroom organization, and instructional support. Each of the domains are further divided in different dimensions of interaction. This study aims to identify which dimensions of instructional support are emphasized in TCI during coding and ER activities of young learners. The video data of 74 young learners (6 years old children) conducting different coding and ER activities in collaboration with their teachers (n =10), was collected from six pre-primary education classrooms. The findings indicate that ensuring young learners’ access to knowledge provided with teachers’ support and instructional exchange was highlighted in teacher-child interaction. We conclude that this support enhances young learners’ participation to the learning process of coding and ER. Implications of instructional support provided by young learners’ teachers are discussed in relation to young learners’ technology education and CDT education, and also in relation to teacher education and training of in-service teachers.
Keywords: instructional support, teacher-child interaction, participation, coding and robotics, young learners